Etiologic factor in the development of myocarditis in the Kharkiv region - Smelyanskaya, M; Peremot, S; Kashpur, N (Annals of Mechnikov's Institute, 2020)
Introduction. According to the research conducted in the last decade, there has been growth in the non-coronary disease infarction among all cardiovascular diseases. The prominent place among all non-coronary heart diseases is taken by myocarditis, which predominantly affects young people of working age (30-40 years old). According to the bibliography, the prevalence of myocarditis is 20% of the non-coronary heart lesions and by different authors 5 - 11% of the total amount of diseases of the cardiovascular system. To date, there are no clear criteria of infectious myocarditis. It is widely accepted that myocarditis is natural complication of infectious diseases in which any infectious agent may be the etiological factor. Until recently, Coxsackie virus of group A, B was considered the most cardiotropic. However, the role of enteroviruses has been recently reviewed in favor of persisting viruses and especially family Herpesviridae. Optimization of myocarditis diagnosis using noninvasive tests, will not only reveal the true extent of the disease but may also enable to examine viral myocarditis as a much more common pathology than it seems at present and will increase understanding of the significance of this pathology in the cardiovascular continuum. Material & methods. 87 people diagnosed with infectious myocarditis were examined. Blood and other biological fluids were subject to examination. Patients of the main group have also had their biopsy material, obtained in a result of endomyocardial biopsy, and pericardial fluid, derived as a result of diagnostic and therapeutic puncture under hydro pericarditis, examined. PCR was performed to determine the genomic sequence of enterovirus (HEV), adenovirus (HAdV), human cytomegalovirus (CMV), herpes simplex virus (HSV), Epstein-Barr virus (EBV), human herpes virus 6 (HHV6) and influenza A viruses and B. Results & discussion. Our research confirms the global trend of reducing the role of enteroviruses in infectious myocarditis. In the course of this investigation, herpesvirus markers in biological material from patients in the form of monoinfection or mixed infections were found in 67 patients with myocarditis, which amounted to 87%. While in the control group, similar markers have been found only in 9 patients or in 22.5% of cases. Herpesvirus detection rate is almost 7 times the allocation of other viruses in infectious myocarditis. Different types of herpesvirus with varying frequency were found in the main (SM and CM) and control groups. According to our data antigens of CMV, HHV6 were found in 60-70% of patients suffering from subacute myocarditis, and almost 40% of patients in this group had markers HSV1,2 and VZV. In patients with chronic myocarditis the percentage of CMV and HHV 6 markers identification reached 70-75%, HSV1,2 - exceeded 50%, EBV - 31,4%. While VZV markers did not much exceed the performance of the control group (16.2% and 12.5% respectively). Determining markers of enteroviruses in the study groups and the control group were not significantly different. Our data detection of mixed infections indicates a very significant (75%) share of the combination of five different herpesvirus in patients with myocarditis. It is predominantly a combination of HHV6 with CMV, HSV1,2, EBV and VZV. The data can be used not only to choose the etiotropic treatment of myocarditis, but also as a diagnostic criteria when combined with a history of clinical indicators. In comparison of herpesvirus DNA detection in patients with SM in blood and EMBS, it was revealed that markers of CMV and HHV6 were almost equally met both in blood and in heart biopsies. Viruses HSV1,2 and VZV were more often detected in the blood than in the EMBS (3 and 1.5 times respectively). This gives reason to believe that the identification of herpesvirus markers in the blood of patients with AM can be used for non-invasive etiological diagnosis of subacute viral myocarditis. Development and introduction into medical practice of new non-invasive methods of myocarditis diagnosis and their etiology specification will enable to examine viral myocarditis as a much more common pathology than it would seem. Conclusion. During virological examination of biological material of myocarditis patients, a high proportion (87%) of antigens of Herpesviridae viruses were revealed. In patients with myocarditis, association of herpesvirus antigens of various types (in 75% of detection) dominate, while in healthy people of the control group - mono infection can be detected more often. Chronic myocarditis patients in 61% of cases are detected with three or four antigens of viruses of the family Herpesviridae, basically HHV6 with CMV, HSV1,2, EBV; with subacute myocarditis – HHV6 with CMV, HSV1,2 and VZV. The findings point to the need for mandatory examination for Herpesviridae virus of patients diagnosed with myocarditis.